DIPLOMASI PREVENTIF KJRI KOTA KINABALU DALAM KASUS HUMAN TRAFFICKING TERHADAP TKI DI SABAH MALAYSIA TAHUN 2014 - Herning Suryo, Ani Kusumarini, ChristyDamayanti & (Transformasi, 2016)
Human trafficking is a form of modern slavery where people profit from the control andexploitation of others and diplomatic effort have been made by the Indonesian government withconduct preventive diplomasi. Almost every country in the world is affected by humantrafficking, whether as a country of origin, transit or destination for victims. The purpose of thisstudi is to determine the preventive diplomacy Consulate General of Republic of Indonesia inKota Kinabalu in the case of human trafficking against Indonesian workers in Sabah Malaysia.The conclude of this research that Workshop Trafficking in Persons as result of bilateraldiplomacy between Consulate General of The Republic of Indonesia with stakeholders inSabah. Multilateral diplomacy conducted by the International Organization such as IOM, ILO,and UNODC produced a basic training that gave recognition that the two members of citizenservice Consulate General in Kota Kinabalu entitled to declare a case as a category of humantrafficking. Through preventive diplomacy conducted Consulate General of The Republic ofIndonesia in Kota Kinabalu, Indonesian workers receive appropriate education and producegood cooperation with Sabah.Key words: diplomacy, illegal, human trafficking